Continuity and Change in Self-Esteem During Emerging Adulthood - Chung, Joanne M. (2013)
The present study examined the development of self-esteem in a sample of emerging adults (N = 295) followed longitudinally over 4 years of college. Six waves of self-esteem data were available. Participants also rated, at the end of their 4th year, the degree to which they thought their self-esteem had changed during college. Rank-order stability was high across all waves of data (Mdn disattenuated correlation = .87). On average, self-esteem levels dropped substantially during the 1st semester (d =−.68), rebounded by the end of the 1st year (d = .73), and then gradually increased over the next 3 years, producing a small (d = .16) but significant mean-level increase in self-esteem from the beginning to the end of college. Individuals who received good grades in college tended to show larger increases in self-esteem. In contrast, individuals who entered college with unrealistically high expectations about their academic achievement tended to show smaller increases in self-esteem, despite beginning college with relatively high self-esteem. With regard to perceived change, 67% reported that their self-esteem increased during college, whereas 12% reported that it declined; these perceptions tended to correspond with actual increases and decreases in their self-esteem scale scores (β= .56). Overall, the findings support the perspective that self-esteem, like other personality characteristics, can change in systematic ways while exhibiting continuity over time.